2020
DOI: 10.5194/hess-2020-431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rainfall-runoff processes in the Loess Plateau, China: Temporal dynamics of event rainfall-runoff characteristics and diagnostic analysis of runoff generation patterns

Abstract: Abstract. The Loess Plateau is the most erosion-prone area in China, while under large-scale ecological restoration runoff and sediments continue to decrease. This study examined the runoff generation mechanism at the catchment scale to understand the change in runoff generation. Six baseflow used to separation method were tested and the nonparametric simple smoothing method was seperating base flow. With the event runoff separation procedure, 340 rainfall–runoff events are selected in five typical catchments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We assume that the simulation occurs in June, July, and August, respectively, then each RC needs to be modified. The runoff coefficients of the permeable areas under the three rainfall events are assigned weighting factors 1.08, 1.09, and 1.10 [39].…”
Section: 𝑞 =mentioning
confidence: 99%
“…We assume that the simulation occurs in June, July, and August, respectively, then each RC needs to be modified. The runoff coefficients of the permeable areas under the three rainfall events are assigned weighting factors 1.08, 1.09, and 1.10 [39].…”
Section: 𝑞 =mentioning
confidence: 99%
“…In contrast, the relationship between SSY and rainfall indices weakened in the later period , which may denote the influence of intensive human interventions on surface hydrological processes. As Wu et al (2020) reported, long-term land use and vegetation changes led to increasing catchment wetness in the LP catchments and a shift to Dunne overland flow regime (Dunne, 1978), which indicated that more rainfall could be intercepted by vegetation cover and leaf litter cover, resulting in higher infiltration and longer travel times (Hu, Zhang, et al, 2020;Hu, Zhao, et al, 2020;L opez-Taraz on et al, 2009;Zhu et al, 2020). For example, an observed event on July 22, 2017 with a basin-averaged rainfall of 82.1 mm, only pro- Among these variables, a strong linear/proportional relationship can be examined between SSY and Q, as confirmed by Zheng (2018).…”
Section: Relationships Of Rainfall Runoff and Suspended Sediment Conc...mentioning
confidence: 99%
“…The flow mechanism corresponding to the rapid response of the stream to the precipitation event is likely due to infiltration excess overland flow rather than saturated overland flow at the study site based on the dry environment and the thick, loess covered characteristics in northern Loess Plateau. 340 rainfall-runoff events were analysed using the event identification method in five typical catchments on the Chinese Loess Plateau (Wu et al, 2020), and also concluded that the Horton overland flow dominates the majority of runoff generation.…”
Section: Flow Mechanismsmentioning
confidence: 99%